A world without privacy : what law can and should do? - Sarat, Austin (Cambridge University Press, 2015)
"Recent revelations about America's National Security Agency offer a stark reminder of the challenges posed by the rise of the digital age for American law. These challenges refigure the meaning of autonomy and the meaning of the word "social" in an age of new modalities of surveillance and social interaction, as well as new reproductive technologies and the biotechnology revolution. Each of these developments seems to portend a world without privacy, or at least a world in which the meaning of privacy is radically transformed, both as a legal idea and a lived reality. Each requires us to rethink the role that law can and should play in responding to today's threats to privacy. Can the law keep up with emerging threats to privacy? Can it provide effective protection against new forms of surveillance? This book offers some answers to these questions. It considers several different understandings of privacy and provides examples of legal responses to the threats to privacy associated with new modalities of surveillance, the rise of digital technology, the excesses of the Bush and Obama administrations, and the continuing war on terror"-- Provided by publisher
Keywords: Privacy, Right of -- United States.; Surveillance detection -- United States.; Détection de surveillance -- États-Unis.; LAW -- Constitutional.; LAW -- Public.; Privacy, Right of; Surveillance detection; United States